‘I decided to attend to him because it’s my duty’: Student Nurses perception and attitude towards care of older adults - Attafuah, P.Y.A.; Amertil, N.; Sarfo, J.O.; Deegbe, D.A.; Nyonator, D.; Amponsah‑Boama, C.; Abuosi, A.A. (BMC, 2022)
Background and Aim: Nurses perception and attitude towards an older patient can positively or negatively influence the quality rendered. As students under training, the views of this population needs to be sought and shaped to improve the quality of care the older patients receive. This is because life expectancy is on the rise. The study aimed to explore students’ perception of ageing and their attitude towards care of the older adults. Methods and materials: An exploratory descriptive design was used. Data form containing the sociodemographic attributes of the students and a semi-structured interview form developed by the researchers in line with the literature. The participants interviewed were student nurses who had been in clinical practice for at least one semester. Four focus group discussions (FGD) were held. Results: Average age of the participants was 22.30 years. An equal number of males and females (15 each) were recruited to have a balance in gender. Students expressed that they saw the older adults as their grandparents so they try to accord them respect and care. However, older adults are perceived not receptive to nurses in training. The students stated that registered nurses neglected the basic care of older adults such as diaper changes, bathing, and feeding, and would rather beckon student nurses to attend to the older adults. Conclusion: Gerontology as a stand-alone course is necessary for early years of training to give an in-depth education to nursing students and instill a positive attitude towards older adult patients.
Research article
Keywords: Career choice; Older adults; Nurse’s attitude; Student perception